Scientific Visual Representations in History
XV, 360 p. 112 illus., 106 illus. in color.
Keywords: This book explores continuity and ruptures in the historical use of visual representations in science and related disciplines such as art history and anthropology. The book also considers more recent developments that attest to the unprecedented importance of scientific visualizations, such as video recordings, animations, simulations, graphs, and enhanced realities. The volume collects historical reflections concerned with the use of visual material, visualization, and vision in science from a historical perspective, ranging across multiple cultures from antiquity until present day. The focus is on visual representations such as drawings, prints, tables, mathematical symbols, photos, data visualizations, mapping processes, and (on a meta-level) visualizations of data extracted from historical sources to visually support the historical research itself. Continuity and ruptures between the past and present use of visual material are presented against the backdrop of the epistemic functions of visual material in science. The function of visual material is defined according to three major epistemic categories: exploration, transformation, and transmission of knowledge.